MORAL VALUES IN THE ENGLISH CHILDREN'S SONG LYRICS - Andreas Heri Kurniawan (Pusat Riset dan Inovasi Nasional, 2021)
The process of build the character can be done by instilling moral values through messages that can be conveyed by parents through various literary media such as, songs, poems, or fairy tales. this study will describe the moral values of humans who relationship with God, self, and with others. This research will use descriptive qualitative method, it means procedure based on descriptive data in the form of oral or written words from research on subjects who have observed and has the characteristics, the data provided is the original data that have been changed by using systematically method and can be accounted for the truth. The data are used from ten English children's songs with the tittle (1) twinkle little star (2) baa baa black sheep (3) you are my sunshine (4) my daddy is the best (5) Please and thank you (6) sorry, excuse me (7) sick song (8) if you’re happy (9) Johny, Johny yes papa (10) Are we there yet? Moral value from human relationship with God, which is obtained from the lyrics of English children's songs relationship with God is a feeling of gratitude for God's power. The moral value of human relations with oneself, in the English children's songs lyrics conveys ways to cultivate self-confidence, joy, and sincere about what happens in this life. moral value that we can get from human Relations with others in English children's song lyrics teach how to behave well with others, respect, and love for others.